Globalization and Labour Reforms in India: A Critical Study: Examining the Impact of Globalization on Workers' Rights in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this era of capitalism, economic neo-liberalism and market-oriented economy under the pretext of economic liberalization and globalization, the rights of workers were limited and social security-network weakened at the practical level, while the profits of corporate groups and business class kept increasing at their cost. . Even the activities of trade unions, which fought for the rights of workers, became limited and changed their agenda. In 2011-12, the informal employment in the organized sector increased from 48 in 2004-05 to 54.6. And, now, in the name of labour reform, under the pretext of economic stagnation, efforts are being made to restrict the rights of workers which they got after a long struggle. The present paper tries to produce a critical study on globalization and labour reforms in India.